(untitled) (Journal of Oriental Studies, 2026)
This study addresses the issue of equal opportunity in the distance education of Turkish as a foreign language and the impact of distance education on the four core language skills. Globalization and rapid advancements in information technology have made distance education a widespread and unavoidable practice in foreign language teaching; however, whether online platforms provide equal opportunity in education, particularly in the context of foreign language teaching, remains a subject of debate. The aim of this study is to review the existing literature on equity of opportunities in the distance education of Turkish as a foreign language and to identify both the strengths and challenges of this process based on instructors’ perspectives. The research was conducted using a descriptive approach that combined both qualitative and quantitative data collection. In this regard, data obtained from a survey administered to 89 instructors working in the field of teaching Turkish to foreigners were analyzed. The results of the survey indicate that distance education can offer vital opportunities in terms of flexibility and accessibility. However, equity of opportunities may not always be achieved because of a lack of technological infrastructure, differences in digital literacy levels, and socioeconomic inequalities. Concerning the four core language skills, the study shows that listening and reading skills can be taught more easily in distance education, while speaking and writing skills can face greater limitations due to a lack of interaction and immediate feedback. Keywords: teaching Turkish as a foreign language, distance education, equity of opportunities, four core language skills.